2022
DOI: 10.3389/fphar.2022.1055911
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in doxorubicin-induced cardiotoxicity: The DNA damage response

Abstract: Doxorubicin (DOX) is a chemotherapeutic drug widely used for cancer treatment, but its use is limited by cardiotoxicity. Although free radicals from redox cycling and free cellular iron have been predominant as the suggested primary pathogenic mechanism, novel evidence has pointed to topoisomerase II inhibition and resultant genotoxic stress as the more fundamental mechanism. Recently, a growing list of microRNAs (miRNAs) has been implicated in DOX-induced cardiotoxicity (DIC). This review summarizes miRNAs re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 211 publications
(299 reference statements)
0
5
0
Order By: Relevance
“…The fact that miRNAs have strong and documented roles in the development of cardiovascular diseases ( Wang, 2010 ; Romaine et al, 2015 ; Barwari et al, 2016 ; Chen et al, 2017 ; Dhingra and Vasan, 2017 ; Peters et al, 2020 ; Laggerbauer and Engelhardt, 2022 ; Gargiulo et al, 2023 ) means that it is expected that miRNAs are involved in the complex pathogenesis of ANT-induced cardiotoxicity. Notably, ANT exposure has already been reported to cause differential expression in various miRNAs (reviewed in Ruggeri et al, 2018b ; Kawano and Adamcova, 2022 ; Yarmohammadi et al, 2023 ; Kuang et al, 2023 ; Chen and Xu, 2021 ; Li et al, 2022 ). Chaudhari et al (2016) described the early deregulation of miR-187-3p, miR-182-5p, miR-486-3p, miR-486-5p, miR-34a-3p, miR-4423-3p, miR-34c-3p, miR-34c-5p, and miR-1303 in iPSCs exposed in vitro to 156 nM doxorubicin (DOX), as well as the prolonged upregulation of miR-182-5p, miR-4423-3p, and miR-34c-5p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that miRNAs have strong and documented roles in the development of cardiovascular diseases ( Wang, 2010 ; Romaine et al, 2015 ; Barwari et al, 2016 ; Chen et al, 2017 ; Dhingra and Vasan, 2017 ; Peters et al, 2020 ; Laggerbauer and Engelhardt, 2022 ; Gargiulo et al, 2023 ) means that it is expected that miRNAs are involved in the complex pathogenesis of ANT-induced cardiotoxicity. Notably, ANT exposure has already been reported to cause differential expression in various miRNAs (reviewed in Ruggeri et al, 2018b ; Kawano and Adamcova, 2022 ; Yarmohammadi et al, 2023 ; Kuang et al, 2023 ; Chen and Xu, 2021 ; Li et al, 2022 ). Chaudhari et al (2016) described the early deregulation of miR-187-3p, miR-182-5p, miR-486-3p, miR-486-5p, miR-34a-3p, miR-4423-3p, miR-34c-3p, miR-34c-5p, and miR-1303 in iPSCs exposed in vitro to 156 nM doxorubicin (DOX), as well as the prolonged upregulation of miR-182-5p, miR-4423-3p, and miR-34c-5p.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, several of the miRNAs which showed significant changes in expression following DAU treatment are related to DDR. This is particularly relevant for members of the miR-34 family ( Kawano and Adamcova, 2022 ; Li et al, 2022 ) as well as miR-504, but—to a certain extent—several others, including the miRNA-21 family, miR-20b-5p, miR-142-3p, and miR-155. Several of these latter miRNAs have been shown to target key mediators of DNA repair and replication in cancer cells, e.g., ATM, ATR, CHK1 and CHK2, DNA-PK, and WEE1 ( Pilié et al, 2019 ), but evidence for these relationships in cardiomyocytes is mostly lacking.…”
Section: Discussionmentioning
confidence: 99%
“…By grafting MPEG5000-NH 2 and DOX onto polysuccinimide, which was obtained by polymerization of l -aspartic acid [152] , and resulting amphiphilic polymer PADO-MPEG self-assembled into nanoparticles. DOX, a commonly used chemotherapy drug [153] , damages DNA by intercalation and complexation with topoisomerase II to enhance radiosensitization [154] , while 5-ALA can target mitochondria [155] and enhance RT. This strategy constructs a mitochondria-targeted radiosensitizer with good biocompatibility and high safety, avoiding the use of complex hybrid nanoparticles.…”
Section: Organelle-targeted Rtmentioning
confidence: 99%
“…Accumulating evidence shows that miRNAs play key roles in the development of cardiovascular diseases, and miRNAs are proposed as potential drug targets for the treatment of human cardiovascular disease [ [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Particularly, miRNAs mediate multiple pathways that are potential targets for cardioprotection against DOX, including p53 signaling, pro-survival signaling, mitochondrial function, etc [ 24 ]. For example, inhibition of miR-140-5p alleviates DOX-induced cardiac myocardial oxidative damage [ 25 ].…”
Section: Introductionmentioning
confidence: 99%